PENGEMBANGAN APLIKASI SMARTOFFICE MENGGUNAKAN METODE WATERFALL UNTUK MENINGKATKAN EFISIENSI PELAYANAN TERPADU SATU PINTU (PTSP) PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAMBI: Smartoffice, PTSP, CAPTCHA, Data Separation, Waterfall - Limia Budiarti, Rike; Megawati, Merti; Khairunissa, Khairunissa (LP2M Universitas Nurdin Hamzah, 2025)
This study discusses the development of the Smartoffice application within the One-Stop Integrated Service (PTSP) section of the Regional Office of the Ministry of Religious Affairs of Jambi Province to improve the efficiency and security of administrative management for incoming letters and diploma legalization. The identified issues include the malfunctioningCAPTCHA code during the login process, which reduces system security, and the absence of data separation between incoming letters and diploma legalization, making document retrieval and management difficult. This research applies the Waterfall methodology, consisting of requirement analysis, system design, implementation, and testing. The development results include fixing the CAPTCHA function, adding data separation basedon service categories, and implementing a more efficient document search feature. The system was implemented using PHP programming language and MySQL database. Testing results indicate that the system improves access security, speeds up document retrieval, andfacilitates officers in managing administrative services digitally.